Belief and belonging in later life: the lived experiences of coping among older Rwandans - Daehnhardt, Madleina (Journal of religion, spirituality & aging, 2022)
This article seeks to give voice to older Rwandans and their experiences of later life. It considers the contribution beliefs make to subjective well-being and coping by analysing self-reported sources of joy and sadness over the life course. The article draws from primary interviews conducted in Kinyarwanda with older Rwandans and church leaders from different denominations. Drawing from the East African context, the analysis contributes to the growing evidence in the field of gerontology showing how important ‘coping mechanisms’ underlie religious faith and practice. The four coping mechanisms identified are: support through personal prayer and resilience, socio-spiritual capital, a sense of belonging and meaning-making, and healthy behaviours influenced by religious values. The findings have implications for African church and national bodies engaged in pastoral care, as well as community organisations working with older people.